Analysis of Digital Literacy in Building Civic Responsibility (Exploratory Study of Interfaith Unity in Semarang City) - Alfiah Alfiah; Triyanto Triyanto; Moh Muchtarom; Laksmi Evasufi Widi Fajari (Peneliti.net, 2023)
The increasing use of social media in Indonesia has actually led to an increase in untrue news, often referred to as hoax news. In addition, social media is often used as a medium for spreading hate speech. So the thing that must be done to overcome these problems is to improve digital literacy to implement civic responsibility in everyone, which is done through the Pelita community in Semarang City. This research provides a literature review of the Pelita community's efforts to build citizens' digital literacy and the role of digital literacy in improving civic responsibility through Pelita. The results show that the Pelita community has provided a basic understanding of digital literacy so that it can increase a sense of civic responsibility.